Modelling of rotations by using matrix solutions of nonlinear wave equations - Gudkov, Vladimir Vasilevich (Mathematical Modelling and Analysis, 2007)
A family of matrix solutions of nonlinear wave equations is extended and its application to modelling is given. It is shown that a similarity transformation, induced by the matrix solution, is equivalent to the rotation. Matrix solutions are used for modelling helical motions and vortex rings, simultaneous rotations and particles collision, mapping contraction and pulsating spheres. Geometrical interpretation of the doubling of rotation angle in each step of sequential mapping contraction is given.First Published Online: 14 Oct 2010